(untitled) (Journal of Applied Oral Science, 2016)
Objectives The aim of this study was to characterise the new hydrophilic fissure sealant, UltraSeal XT® hydro™ (Ultradent Products, USA), and to investigate its in vitro resistance to microleakage after placement on conventionally acid etched and sequentially lased and acid etched molars. Material and Methods The sealant was characterised by Fourier transform infra-red spectroscopy (FTIR), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), and Vickers indentation test. Occlusal surfaces of extracted human molars were either conventionally acid etched (n=10), or sequentially acid etched and laser irradiated (n=10). UltraSeal XT® hydro™ was applied to both groups of teeth which were then subjected to 2,500 thermocycles between 5 and 55°C prior to microleakage assessment by fuchsin dye penetration. Results UltraSeal XT® hydro™ is an acrylate-based sealant that achieved a degree of conversion of 50.6±2.2% and a Vickers microhardness of 24.2±1.5 under standard light curing (1,000 mWcm-2 for 20 s). Fluoride ion release is negligible within a 14-day period. SEM and EDX analyses indicated that the sealant comprises irregular submicron and nano-sized silicon-, barium-, and aluminium-bearing filler phases embedded in a ductile matrix. Laser preconditioning was found to significantly reduce microleakage (Mann-Whitney U test, p